Mechanistic insight of TiCl4 catalyzed formal [3 + 3] cyclization of 1, 3-bis(silyl enol ethers) with 1, 3-dielectrophiles. Issue 114 (3rd November 2015) - Nisa, Riffat Un; Maria; Wasim, Fatima; Mahmood, Tariq; Ludwig, Ralf; Ayub, Khurshid
Abstract : The mechanism of TiCl4 mediated formal [3 + 3] cyclization of 1, 3-bis(silyl enol ethers) with 1, 3-dielectrophiles is studied at the B3LYP level of density functional theory (DFT) to rationalize the experimental regioselectivity. Abstract : The mechanism of TiCl4 mediated formal [3 + 3] cyclization of 1, 3-bis(silyl enol ethers) with 1, 3-dielectrophiles is studied at the B3LYP level of density functional theory (DFT) to rationalize the experimental regioselectivity. Methyl and trifluoromethyl substituted 1, 3 dielectrophiles are studied theoretically since they show different regioselectivities. Two different mechanisms involving 1, 2 and 1, 4 addition of 1, 3-bis(silyl enol ethers) on 1, 3-dielectrophiles are studied for each dienophile. The intramolecular transition metal catalyzed and non-catalyzed dynamic shift of the silyl moiety is also studied. The structure of the 1, 3 dienophile and the associated Mulliken charges are the driving forces for different regioselectivities in methyl and trifluoromethyl dienophiles.